A study of the influence of plasmonic resonance of gold nanoparticle doped PEDOT: PSS on the performance of organic solar cells based on CuPc/C60. Issue 11 (November 2019) - Said, D.A.; Ali, A.M.; Khayyat, M.M.; Boustimi, M.; Loulou, M.; Seoudi, R.
Abstract: This work studied the role of gold nanoparticles (AuNPs) with different spherical sizes mixed with poly (3, 4-ethylene dioxythiophene): polystyrene sulfonate (PEDOT: PSS) as a hole transfer layer to enhance the efficiency (ITO/PEDOT:PSS (AuNPs)/CuPc/C60 /Al) organic photovoltaic cell (OPV). AuNPs were synthesized using the thermochemical method and the results of the transmission electron microscope (TEM) images showed that the gold nanoparticles mostly dominated by spherical shapes and sizes were calculated in the range (12–23 nm). Measurements of UV-VIS spectra for AuNPs have shown that the surface plasmon resonance shifted to a higher wavelength with decreasing the particle size. Surface morphology and absorption spectra of OPV cells were studied using atomic force microscope and UV-VIS spectrometer techniques. The efficiency of the OPV cell was calculated without and with AuNPs. Efficiency was increased from 0.78% to 1.02% due to the embedded of AuNPs with (12 nm) in PEDOT/PSS. The increase in the light absorption in CuPc is due to the good transparent conducting of PEDOT:PSS and the increase in the electric field around AuNPs embedded in PEDOT:PSS and inbuilt electric field at the interfacial between CuPc and C60 is due to the surface plasmon resonance of AuNPs. The increase in these two factors increase the exciton generation in CuPc, dissociation at the interfacial layer, and charge carrier transfer which increases the collection of electrons and holes at cathode and anode. Abstract : Materials science; Materials chemistry; Copper phthalocyanine; Gold nanoparticles; Fullerene; Solar cell; PEDOT:PSS